Algorithms for accurate collection, ejection, and loading in particle simulations - Kim, H.C.; Feng, Y.; Verboncoeur, J.P. (Journal of computational physics, 2007)
Algorithms for accurate collection, ejection, and loading of particles in particle simulations are presented. The algorithm for particle collection finds the position and velocity at any specific time from those at a discrete time. The algorithms for particle ejection and loading find the value at a discrete time from those at a given time. The accuracy of these algorithms is analyzed for general fields and is confirmed by comparing the numerically computed value with its exact solution under a homogeneous magnetic field. In particular, this ejection method can be applied to secondary emission as well as spontaneous emission.